Carbondioxide-Aided Angiography Decreases Contrast Volume and Preserves Kidney Function in Peripheral Vascular Interventions. (October 2016) - Stegemann, Emilia; Tegtmeier, Catharina; Bimpong-Buta, Nana Yaw; Sansone, Roberto; Uhlenbruch, Mark; Richter, Andreas; Stegemann, Berthold; Roden, Michael; Westenfeld, Ralf; Kelm, Malte; Heiss, Christian
Chronic kidney disease is a common comorbidity in patients with peripheral artery disease. We investigated the safety and efficacy of carbon dioxide (CO2 ) as supplemental contrast agent to decrease contrast volume during fluoroscopy-guided peripheral vascular procedures in routine angiological practice. We analyzed 191 consecutive interventions of the lower extremity in claudicants and critical limb ischemia (CLI) that were performed with iodinated contrast media (ICM) alone (n = 154) or with the aided or exclusive use of CO2 (n = 37). The technical success rate, total irradiation, and intervention time were not significantly different between ICM and CO2 . No severe procedure-related complications occurred. The contrast volume was lower in CO2 than in ICM. Although kidney function, creatinine, and estimated glomerular filtration rate was lower in CO2 at baseline, the incidence of contrast-induced nephropathy was lower in CO2 compared to ICM. These data support CO2 as an alternative supplemental contrast agent that can be applied safely and efficiently to lower contrast volume during peripheral vascular interventions preventing kidney dysfunction even in patients with disease of the popliteal artery and below the knee and CLI.